Cytotoxic polyketides from the deep-sea-derived fungus Aspergillus fischeri FS452. Issue 22 (17th November 2022) - Liu, Zhaoming; Li, Saini; Chen, Yuchan; Li, Mingqiong; Liu, Hongxin; Zhang, Weimin
Abstract: Six globoscin derivatives (1 ‒6 ) including two new ones fischerins A (1 ) and B (2 ) were isolated from the deep-sea-derived fungus Aspergillus fischeri FS452. Their structures were elucidated by comprehensive spectroscopic analysis and the absolute configurations were determined by the quantum chemical ECD calculations. The in vitro cytotoxicity assays indicated that fischerin B (2 ) exhibited potential activities against the four tested human cancer cell lines (SF-268, MCF-7, HepG-2 and A549) with the IC50 values in the range of 7–10 µM. Graphical Abstract: UF0001